Strategi Pemanfaatan Sosial Media sebagai Promosi di Masa Pandemi Covid 19 pada UKM Bolenku Kabupaten Kulon Progo (STIE Rajawali Purworejo, 2024)
This study aims to explain how the use of social media as a promotional strategy uses a qualitative descriptive approach with the object of research at UKM BolenKu Kulon Progo during the covid19 pandemic. This study explains how the use of social media as a promotional strategy in UKM BolenKu Kulon Progo based on a SWOT analysis and which strategy is most suitable to be chosen considering the amount of market competition and the difficulty of selling during the covid19 pandemic. The primary data used in this study were obtained directly from the owners of UKM BolenKu, employees and consumers/followers. The analytical method used is SWOT analysis, SWOT matrix and SWOT diagrams. The results of the analysis of this study are the use of social media as a promotional strategy is very helpful in developing the UKM BolenKu Kulon Progo business and the strategy used is an aggressive strategy or market penetration.